The Impact of Hydroxyethyl Starch Use in Deceased Organ Donors on the Development of Delayed Graft Function in Kidney Transplant Recipients: A Propensity‐Adjusted Analysis. Issue 8 (22nd April 2015) - Patel, M. S.; Niemann, C. U.; Sally, M. B.; De La Cruz, S.; Zatarain, J.; Ewing, T.; Crutchfield, M.; Enestvedt, C. K.; Malinoski, D. J.
<x xml:space="preserve">Abstract</x> Our objective was to evaluate the impact of hydroxyethyl starch (HES) use in organ donors after neurologic determination of death (DNDD) on recipient renal graft outcomes. The following data elements were prospectively collected for every DNDD managed by a single organ procurement organization from June 2011 to July 2013: demographics; critical care endpoints; treatments, including the use of HES; graft cold ischemia time (CIT); and the occurrence of recipient delayed graft function (DGF, dialysis in the first week after transplantation). Logistic regression was performed to identify independent predictors of DGF with a p‐value <0.05. The results were then adjusted for each donor's calculated propensity to receive HES. Nine hundred eighty‐six kidneys were transplanted from 529 donors. Forty‐two percent received HES (1217 ± 528 mL) and 35% developed DGF. Kidneys from DNDDs who received HES had a higher crude rate of DGF (41% vs. 31%, p < 0.001). After accounting for the propensity to receive HES, independent predictors of DGF were age (OR 1.02 [1.01–1.04] per year), CIT (OR 1.04[1.02–1.06] per hour), creatinine (OR 1.5 [1.32–1.72] per mg/dL) and HES use (OR 1.41 [1.02–1.95]). HES use during donor management was independently associated with a 41% increase in the risk of DGF in kidney transplant recipients.